Monolithic nanoporous NiFe alloy by dealloying laser processed NiFeAl as electrocatalyst toward oxygen evolution reaction. (9th August 2018) - Cui, Xiaodan; Zhang, Boliang; Zeng, Congyuan; Wen, Hao; Guo, Shengmin
Abstract: In this paper, monolithic nanoporous NiFe electrocatalyst is developed by dealloying a NiFeAl alloy, fabricated by a laser-based manufacturing method, as the electrocatalyst toward oxygen evolution reaction (OER). The nanoporous NiFe alloy displays an improved electrochemical performance by exhibiting an OER current density of 100 mA/cm 2 at 442 mV overpotential in the 1 M KOH aqueous solution, which is better than that of laser processed bulk NiFe alloy (464 mV). The structures, crystallinities, and chemical compositions of the nanoporous NiFe electrocatalyst are characterized by SEM, XRD and EDXS. With an activity comparable to the electrocatalysts reported to date, the monolithic nanoporous NiFe electrodes are also highly flexible in mechanical configurations, due to the combined advantages of both laser and dealloying processes, which provide new options for OER electrode design. Highlights: Monolithic nanoporous NiFe electrocatalyst is developed by dealloying a laser processed NiFeAl alloy. The nanoporous NiFe alloy displays an improved OER performance than solid NiFe alloy. The dealloying process generates more mass diffusion pathways and active catalytic sites. The combined laser manufacturing and dealloying process is flexible in electrode structural design and optimization.